High‐frequency whistles of Irrawaddy dolphins (Orcaella brevirostris) recorded in Brunei Bay. Issue 3 (24th February 2020) - Jiang, Ying; Liu, Zongwei; Yang, Chunmei; Lü, Lian‐gang; Yu, Xiaolin; Huang, Longfei; Zhang, Xuelei; Yang, Zhiguo; Yang, Guangbing; Sun, Lu; Jaaman, Saifullah Arifin; Muda, Azmi Marzuki
Abstract: Studies of the whistles of Irrawaddy dolphins ( Orcaella brevirostris ) have traditionally been restricted to analyses of the human audio range (below 20 kHz). In this study, broadband acoustic recordings of Irrawaddy dolphins in Brunei Bay were obtained using a sampling frequency of 512 kHz. Among the 984 whistles collected, eight (0.81%) high‐frequency whistles were detected with fundamentals above 18.4 kHz, which is the reported maximum frequency. Four (50%) of these whistles had the entire fundamentals in the ultrasonic frequency range (above 20 kHz), where 52.3 kHz was the maximum frequency. This is the first description of the ultrasonic components of Irrawaddy dolphin whistles. Our findings demonstrate that the whistles of Irrawaddy dolphins span a wider frequency range than previously published.